Development of shear connections in steel-concrete composite structures = Rozwój połączeń ścinanych w stalowo-betonowych konstrukcjach zespolonych - Biegus, Antoni; Lorenc, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Different types of shear connectors and modelling techniques are presented. Basic research conducted or presented after year 2000 is taken into consideration, following the idea of concrete dowel implemented in the form of perfobond strip at the beginning of the 1980s by F. Leonhardt. The latest research in the field of continuous shear connectors applied in bridges is high lited with special focus at the composite dowel shear connection, as it seems to be the most modern solution being strongly introduced to the industry. Final shape of composite dowel shear connection is presented.
Keywords: konstrukcje stalowo-betonowe; belka zespolona; połączenie ścinane; steel-concrete structures; composite beam; composite dowels; shear connection